1985
DOI: 10.1017/s0022172400060769
|View full text |Cite
|
Sign up to set email alerts
|

The basic phage set for typing bovine staphylococci

Abstract: Two hundred and sixty-nine Staphylococcus aureus cultures isolated from bovine milk were subjected to phage typing using the International basic set of 16 phages at Routine Test Dilution. In the current study 73.6% of cultures were 'typable' compared with 84-89% in 1972 when the set was first recommended. The set remains capable of typing the majority of bovine staphylococci but shows a reduction in lysogenicity of most of its phages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Biotyping, serotyping, phage typing and plasmid pattern analysis have been used for epidemiological studies of S. aureus [4][5][6][7]. However, these methods are not without limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biotyping, serotyping, phage typing and plasmid pattern analysis have been used for epidemiological studies of S. aureus [4][5][6][7]. However, these methods are not without limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Using a set of 16 phages at routine test dilution resulted in 84-9 % typability of S. aureus [7]. When the international basic set of phages were subsequently tested only 73-6 % of S. aureus isolates were typeable [4]. Matthews and co-workers [5] recently reported on plasmid profile analysis for discriminating between isolates of Staphylococcus species and concluded that plasmid profile analysis was not an adequate method for differentiating isolates of Staphylococcus species recovered frequently from bovine milk.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the cultures used came from widely distributed geographical locations to minimize indigenous-influences that might affect a native population of organisms relative to their susceptibility to phage (Carrol and Francis 1985). Phages were isolated by enriching individual 100-mL, untreated sewage samples, obtained from local treatment plants during different seasons of the year.…”
Section: 'mentioning
confidence: 99%
“…To date, phage sets have been reported for a number of microorganisms, including Staphylococcus aureus of both human (Fisk 1942a(Fisk , 1942bFelix and Callow 1956;Blair and Williams 1961) and animal origin (Davidson 1961;Blouse and Meekins 1968;Carrol and Francis 1985;Shimizu 1977), S. epidermidis (Talbot and Parisi 1977;Verhoef et al 1972), Escherichia coli (Gershman et al 1984), Salmonella typhimurium (Callow 1959;Wilson et al 1971), and a single set for characterizing salmonellae in general (Gershman and Markowsky 1983).…”
mentioning
confidence: 99%
“…Molecular typing techniques have also been applied for epidemiological studies of 5. uureus (MATTHKWS et al, 1994;AARIISTRUP et al, 1995;FITZ-GEM1.D et al, 1997). The international phage set (IPS) for typing human strains of .I: uureus has been determined also to be useful in typing strains o f ,I: aureus of animal origin (SI IIMIZU et al, 1979;PARKER, 1983;CARROIJ. and FRANCIS, 1985;SWARTZ et al, 1985).…”
Section: Introductionmentioning
confidence: 99%